2021
DOI: 10.3390/jcm10245741
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic and Antidepressant Use and Burnout: Optimism as a Mediator in Spanish Nurses

Abstract: The aim of this study was to analyze the relationship between burnout, the use of drugs (anxiolytics and antidepressants) and optimism in nurses. At the end of 2018, a cross-sectional descriptive study was carried out with a sample of actively employed nurses recruited by snowball sampling. The sample consisted of 1432 nurses in Andalusia (Spain), aged 22–58, who were working at the time of data collection, 83.2% of whom were women. Data were collected anonymously in an ad hoc questionnaire about sociodemograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
3
0
2
Order By: Relevance
“…It was also observed that the use of anxiolytics and the help of a psychiatrist are related to each other, since among the 41 subjects who use anxiolytics, and they sought the help of a psychiatrist, there were 12 who use anxiolytics with the help of a psychiatrist, and 29 of them who use them without the help of a psychiatrist. Such results are somewhat worrying and are in favor of numerous studies already conducted on this topic, according to which health care workers are prone to addictions to anxiolytics because they are easily accessible and are not controlled when taking them, and often take them on their own ( 8 , 27–29 ). The interdependence of the frequency of taking anxiolytics and the overall experience of stress showed a statistically significant difference, i.e., that people who use anxiolytics have on average more points on the stress perception test than those who do not apply them.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was also observed that the use of anxiolytics and the help of a psychiatrist are related to each other, since among the 41 subjects who use anxiolytics, and they sought the help of a psychiatrist, there were 12 who use anxiolytics with the help of a psychiatrist, and 29 of them who use them without the help of a psychiatrist. Such results are somewhat worrying and are in favor of numerous studies already conducted on this topic, according to which health care workers are prone to addictions to anxiolytics because they are easily accessible and are not controlled when taking them, and often take them on their own ( 8 , 27–29 ). The interdependence of the frequency of taking anxiolytics and the overall experience of stress showed a statistically significant difference, i.e., that people who use anxiolytics have on average more points on the stress perception test than those who do not apply them.…”
Section: Discussionmentioning
confidence: 91%
“…This link between seniority and age can also be explained by burnout syndrome at work. Burnout occurs after a long period of time working in one profession ( 27 ). In a study of the interrelationship between the use of anxiolytics and the seeking of psychiatric assistance, Fisher’s exact test showed statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Posledično je bila ugotovljena tudi rast porabe zdravil za zdravljenje duševnih in vedenjskih motenj. Na primer, v Španiji ugotavljajo, da je izmed 1548 anketiranih medicinskih sester, kar 521 (34 %) uporabljalo anksiolitike (Martos Martínez, et al, 2021).…”
Section: Discussionunclassified
“…Among them are high rates of absenteeism, turnover, and suicide among healthcare professionals (Chirico & Leiter, 2022). In turn, burnout stemming from violence against nurses is directly related to negative health results (Havaei et al, 2020; Martos et al, 2021). It is therefore not surprising that burnout is a variable of special interest in the healthcare environment (Barragán et al, 2020; Chirico, Afolabi, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%